1975
DOI: 10.1161/01.res.36.6.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged low-dose angiotensin II infusion on the sensitivity of adrenal cortex in man.

Abstract: The effect of incremental infusions of isoleucine-5-angiotensin II on blood pressure and plasma aldosterone concentrations was studied in normal man before and after 66 hours of intravenous infusion of angiotensin II at 2 ng kg-1 min-1, sodium and potassium balance being kept roughly constant throughout. Plasma sodium and ACTH concentrations were unaltered, but plasma potassium and magnesium levels and basal plasma cortisol fell slightly after prolonged angiotensin administration. During the prolonged angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
21
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 0 publications
4
21
0
Order By: Relevance
“…20 ' 21 Since chronic administration of renin or A II has a sensitizing effect on the adrenocortical zona glomerulosa, 1722 it is presumed that the renin-angiotensin system mediates changes in adrenocortical sensitivity during alterations in sodium intake, although other factors apparently are involved also. 17 However, if changes in adrenocortical sensitivity do in fact account for any part of the differential aldosterone response observed in the present study, one might expect the sensitivity changes not to be mediated by the renin-angiotensin system since this feedback loop was fixed at the same level in both experiments by 7 days of A II infusion. On the other hand, the prolonged suppression of the renin-angiotensin system prior to infusion of AII in experiment 3 (Fig.…”
mentioning
confidence: 58%
“…20 ' 21 Since chronic administration of renin or A II has a sensitizing effect on the adrenocortical zona glomerulosa, 1722 it is presumed that the renin-angiotensin system mediates changes in adrenocortical sensitivity during alterations in sodium intake, although other factors apparently are involved also. 17 However, if changes in adrenocortical sensitivity do in fact account for any part of the differential aldosterone response observed in the present study, one might expect the sensitivity changes not to be mediated by the renin-angiotensin system since this feedback loop was fixed at the same level in both experiments by 7 days of A II infusion. On the other hand, the prolonged suppression of the renin-angiotensin system prior to infusion of AII in experiment 3 (Fig.…”
mentioning
confidence: 58%
“…Here also a discrepancy has been noted, between the effect of angiotensin II infusions on aldosterone secretion in normal animals and the larger aldosterone responses caused by sodium deficiency (6, 7). However, the sensitivity of the adrenal to angiotensin II in several species increases during sodium restriction (8)(9)(10)(11)(12), and this could contribute to the relatively greater aldosterone secretion that accompanies the increased blood concentrations of angiotensin II during sodium deficiency.The interaction between angiotensin II and altered adrenal sensitivity during the aldosterone response to sodium restriction has been recently analyzed in rats. Initial studies showed that prolonged changes in electrolyte intake were accompanied by altered affinity and concentration of angiotensin II receptors in the rat adrenal (13).…”
mentioning
confidence: 99%
“…The long-term plasma angiotensin levels determine the ability of the adrenal to secrete aldosterone (Sealey et al, 1978). When angiotensin II levels are high, aldosterone secretion is augmented (Hallenberg et al, 1974;Oelkers et al, 1975). Therefore, the high endogenous levels of renin and angiotensin in the newborn lamb may be responsible for the greater renin inhibitory and aldosterone stimulatory responses seen in the newborn lamb compared to the non-activated reninangiotensin system in the ewe (P < 0.01) (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, pressor responsiveness varies with sodium and potassium balance (Hollenberg et al, 1975;Reid and Laragh, 1965), plasma renin and angiotensin II levels (Chinn and Dusterdieck, 1972), and prostaglandin concentrations (Hall et al, 1978). Adrenal aldosterone release responsiveness to ACTH, angiotensin II, and potassium seems to be positively dependent both on the steady state (Sealey et al, 1978) and acute level of angiotensin II (Hollenberg et al, 1974;Oelkers et al, 1975). Kidney renin content and renin release are augmented with high levels of angiotensin II (Flamenbaum and Hamburger, 1974;Fray, 1978).…”
mentioning
confidence: 99%